2011
DOI: 10.4314/thrb.v13i2.62980
|View full text |Cite
|
Sign up to set email alerts
|

Defining malaria burden from morbidity and mortality records, self treatment practices and serological data in Magugu, Babati District, northern Tanzania

Abstract: Malaria morbidity and mortality data from clinical records provide essential information towards defining disease burden in the area and for planning control strategies, but should be augmented with data on transmission intensity and serological data as measures for exposure to malaria. The objective of this study was to estimate the malaria burden based on serological data and prevalence of malaria, and compare it with existing self-treatment practices in Magugu in Babati District of northern Tanzania. Prospe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 39 publications
1
7
0
Order By: Relevance
“…This study also found no Plasmodium infection in Magugu, which means that the prevalence might be at a very low rate, despite a favorable and suggestive climate for malaria endemicity. This result is in confluence with a previous study which also reported low prevalence of malaria in Magugu 23 and with National Malaria Survey which reported prevalence of <1% in Manyara region 24 . Zero prevalence of Plasmodium infection reported from Magugu by this study, can be explained from different perspectives, one of which could be the use of Magugu site as a trial site for pesticide efficacy studies.…”
Section: Discussionsupporting
confidence: 90%
“…This study also found no Plasmodium infection in Magugu, which means that the prevalence might be at a very low rate, despite a favorable and suggestive climate for malaria endemicity. This result is in confluence with a previous study which also reported low prevalence of malaria in Magugu 23 and with National Malaria Survey which reported prevalence of <1% in Manyara region 24 . Zero prevalence of Plasmodium infection reported from Magugu by this study, can be explained from different perspectives, one of which could be the use of Magugu site as a trial site for pesticide efficacy studies.…”
Section: Discussionsupporting
confidence: 90%
“…Diagnoses are frequently provisional in the absence of adequate confirmatory tests, and it is, therefore, a common practice that antimicrobials are irrationally prescribed, leading to serious consequences, including the development of antimicrobial resistance. 20,21 This scenario justifies the application of high-throughput and highly sensitive molecular tools to determine the causes of diseases with overlapping clinical signs and for proper management of febrile illness. About half of the participants in Bondo had P. falciparum parasitaemia.…”
Section: Discussionmentioning
confidence: 99%
“…Support for malaria control at both the national and district levels has increased considerably over the past few years. The low prevalence of P. falciparum infection in Magugu has been reported for about a decade, 11,20,24 likely because Magugu serves as an experimental study site for a national pesticide research institute. 25 The prevalence of S. typhi infection in Bondo was high, with about one-fifth of the population testing positive for S. typhi, while in Magugu, about one-tenth of individuals were found to be infected with S. typhi.…”
Section: Discussionmentioning
confidence: 99%
“…We did observe quite a low number of mRDT positives in the 3 sites; preliminary data suggest that, as expected, a fraction of the mRDT negatives are plasmodium positive when using a sensitive PCR method (data not shown), and therefore the low parasitaemi as are having no impact on fever/symptoms observed in participants, nevertheless after excluding all malaria positive, we found that 38.0 % of the remaining participants reported fever. It is known that in many malaria endemic areas where clear diagnosis cannot be established, all fevers may still be treated as malaria [ 53 ]. Therefore, we recommend establishment of better diagnosis of fever to avoid over-treatment of other diseases.…”
Section: Discussionmentioning
confidence: 99%